74 Analysis of IGE, IGE Rast Value and Prick Test in Wheat or Hen's Egg-Allergy Infants Treated with Slow Specific Oral Tolerance Induction Therapy - Noma, Takeshi (World Allergy Organization Journal, 2012)
BACKGROUND: Food allergy primarily causes anaphylaxis in children. Food such as egg, cow milk, wheat and peanut are common allergen in Japan. METHODS: In this study total IgE, IgE RAST value and prick test are evaluated to monitor the efficacy outcome in wheat or hen's egg-allergy infants treated with slow specific oral tolerance induction (sSOTI) therapy. RESULTS: The 3 infants suffered from IgE-mediated food allergy (wheat: 2 years 8 or 10 months old boy [threshold dose 25 g] and girl [0.7 g], hen's egg: 4 years 9 months old girl [1.8 g]), diagnosed, by food challenge, as allergy to wheat and egg. Then, the patients were treated with sSOTI either with hard-boiled egg or wheat noodle at home daily starting with 0.1 g, respectively, increased to a dose of 60 g egg or 100 g wheat, every one to 2 weeks in double dose of the weight, until tolerance was taken on. The daily maintenance dose was 10 g for each food. Four weeks later confirmed was evolution of tolerance by re-challenge. The safety and efficacy of the sSOTI therapy were confirmed in these infants. Total IgE levels were increased after SOTI therapy whereas IgE RAST value to causative antigen such as egg and wheat, contrastingly reduced. IgE RAST value to some other food as cow's milk, reduced coincidently by bystander inhibition. IgE RAST value to a food, negative in prick test, was increased again, whereas that to a food, positive in the test, was carried on. CONCLUSIONS: The results indicates that sSOTI therapy induced causative antigen-specific IgE-mediated tolerance in children with wheat or egg allergy, and the set of total IgE increased, reduced IgE RAST value and positive prick test was of service to evaluate evolution of tolerance in slow SOTI therapy.